"It doesn't stop when you get to 18": experiences of self-harm in adults. Issue 4 (12th July 2021) - Boyce, Melanie
Abstract : Purpose: Self-harm can affect people of all ages, yet the high prevalence rate in adolescents and the potential risk factor of suicide in adults 60 years and above has meant research has tended to focus within these areas. Therefore, the purpose of this exploratory study is to examine the experiences of self-harm in people from early adulthood to late middle age to gain greater insight and understanding in this underexplored area. Design/methodology/approach: An online open-ended survey was used to collect the data from a UK user-led moderated online forum that supports people who self-harm. Findings: Thematic data analysis indicates that feelings of shame and guilt were intensified, due to the double stigma participants face as adults that self-harm. Although most participants had seen a reduction in the frequency of their self-harm many experienced an increase in the severity of harm. In not fitting the assumed typical profile of someone that self-harm participants often struggled to gain formal support. Research limitations/implications: This was a small-scale online survey; hence, it is not possible to generalise the findings to all adults who self-harm. Practical implications: The findings from this research provide evidence that greater recognition needs to be given to the reality that self-harm can affect people of all ages. As a result, access to support needs to be widened as a means of supporting those who do not fit the typical profile of someone who self-harms. Originality/value: This exploratory online study provides insights around the tensions and challenges facing adults that self-harm, which remains an under-researched and largely ignored area.